Pelatihan dan Pendampingan Digital Marketing sebagai upaya Peningkatan Omset pada UMKM Arista Desa Kalianget Timur Kec.Kalianget Kab.Sumenep - Dewi Wulansari; Fadilah Tri Wahyuni (Universitas Kristen Indonesia Toraja, 2025)
The advancement of information technology has a major impact on life, especially in the business world. Business in the current era can no longer be run like in the past. Technology is a mainstay in running a business today which changes the direction of digital product marketing practices or digital marketing. Digital marketing opens communication between potential consumers and sellers that can be done without distance and time constraints. However, the facts on the ground state that there are still some MSMEs that only rely on conventional marketing activities by opening shops to serve consumers/buyers face to face directly. In the current digital era, these MSME actors have not utilized technology to carry out digital marketing, so the number of consumers is limited only to the area around the MSME. This community service aims to expand the reach of sales and increase the sales turnover of ARISTA MSMEs in Kalianget Timur Village, Kalianget District, Sumenep Regency through training and mentoring using digital marketing. This community service activity uses a qualitative method as an approach to the case with ARISTA MSMEs engaged in the home industry of kitchen equipment. The output of this service includes having an online store on social media (Instagram and Facebook) as a digital marketing strategy so that it can expand sales reach and increase sales turnover for ARISTA MSMEs.